JURIDICAL IMPLICATIONS OF USING CRYPTOCURRENCY AS A PAYMENT TOOL - Kurniawan, Itok Dwi (PT. Altin Riset Publishing, 2024)
This article aims to analyze the use of cryptocurrency as a substitute for conventional currency in Indonesia. The article is written using normative legal research methods with conceptual and legislative approaches. The results of this research indicate that cryptocurrency can be considered as a solution for a different level of payment system; however, the demand for this type of cryptocurrency is not proportionate to its supply. As a result, cryptocurrency is unlikely to become an everyday payment tool but may serve as a more specific means of payment or exchange at a certain level. Currently, cryptocurrency can only function as an investment tool that is bought and sold, making it challenging when directly compared to traditional currency for daily payment purposes. The opportunity for cryptocurrency to replace conventional currency in Indonesia is very small. This is due to the unstable (highly fluctuating) value of cryptocurrency and the absence of an authority determining its value.